If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -1(-71) = 74 Multiply -1 * -71 k + 71 = 74 Reorder the terms: 71 + k = 74 Solving 71 + k = 74 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-71' to each side of the equation. 71 + -71 + k = 74 + -71 Combine like terms: 71 + -71 = 0 0 + k = 74 + -71 k = 74 + -71 Combine like terms: 74 + -71 = 3 k = 3 Simplifying k = 3
| c-78=(-10) | | 9x^2=-77+18x | | x^3-10x=-3x^2-24 | | j+4=(-85) | | -87=g-92 | | 2a-3b(a-5)=5 | | w+27=(-64) | | 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 | | q-(-9)=73 | | 14c-7d= | | 98=-7z | | 2v-15=25 | | -15=w-62 | | 3x+14=-7+2x | | -4n=(-64) | | 10x^2+81x+8=0 | | h+(-91)=6 | | -8j=88 | | c^2-3c-85=0 | | 10x-11-8x+23=6 | | -9h=-99 | | b-(-12)=15 | | -4u-2(-u-15)=8(2u-9) | | 3=j+-9 | | 17=c-(-7) | | 6n^2+29n+28=0 | | 3Cosx=3 | | 12=-4g | | 6x-10-4x+13=-2 |